Дослідження та популяризація творчості мовознавця з Волині Миколая Крушевського - Пахолок, З. (Краєзнавство, 2019)
Стаття присвячена вивченню й поширенню інформації про життєвий шлях та науковий доробок
мовознавця, уродженця Луцька Миколая Крушевського, доля якого внаслідок історичних умов повʼязана
з Україною, Польщею, Росією. Акцент зроблено на волинському періоді буття представника польського
роду. Подано власні публікації авторки, з-поміж яких здійснено перший українськомовний переклад, опубліковано епістолярну спадщину мовознавця та перевидані дві його праці; представлено виступи на
радіо, кіно- і телесценарії, випуск настільного календаря і конверта, введення до наукового обігу
фотографій із родинного архіву Крушевських.
Значення проведеного дослідження обумовлено архівним сегментом джерельної бази. Соціальний
резонанс відображено у музейних виставках та ювілейному вшануванні вченого; презентаціях і рецензіях на перевидання творів та книг про нього; відгуках на дослідження авторки; підготовці репринтного видання; створенні портретів та скульптурного зображення мовознавця; подяк за активну діяльність у популяризації історії волинського краю; представленні на обласну премію в галузі літератури,
культури і мистецтва і нагородженні дипломом імені академіка Миколи Державіна.
Перспектива подальших студіювань повʼязана із продовженням вивчення родини мовознавця та
підготовці українськомовного перекладу його наукової спадщини. The article deals with the study of Lutsk Mikolaj Kruszewski, the native figure, whose fate is connected with
different countries according to the historical conditions. He was the representative of the Polish family and
spent his childhood and adolescence in Ukraine, mainly in Solotvin and Kovel. Mikolaj studied at the Lutsk
Noble School, but his youth was spent in Poland, where he studied at Kholm High School and Warsaw University.
His mature years were connected with Russia, because he was the teacher of Troitsk Gymnasium and Kazan
University. His scientific work was aimed at the problems of Phonetics and Morphology of General Linguistics.
Mikolaj’s main publications may be characterised in the following way: the first Ukrainian translation
was made; the epistolary legacy of the linguist and his two works were published; presentations on radio, film
and television scripts were introduced, the release of desktop calendar and the envelope, introduction to the
scientific circulation of photographs from the Kruszewskiʼs family archive are represented, etc.
The value of the study determined the archival segment of the source base. The social resonance on the
activity of the author is reflected in museum exhibitions and the jubilee commemoration of the scholar; presentations
and reviews on re-releases of works and books about him; reviews of the author’s researches; preparation
of the reprint edition; creation of portraits and sculptural image of linguist; gratitude to the scholar for
his activity in promoting the history of Volyn region; presentation at the regional prize in the field of literature,
culture and art, awarding with the academician Mykola Derzhavin diploma.
The prospect of further research is connected with the continuation of the study of the linguistʼs family and
preparation of the translation of his scientific heritage from Russian into Ukrainian language.